26.3k views
4 votes
Solve this nonlinear system of equations.

y=-x^2+6x-5
y=3
step 1: use substitution to combine the equations. Rewrite so that one side is equal to zero.
step 2: factor the equation
step 3: identify the x-values of the solutions.
step 4: identify the solutions to the system.

User Tinthetub
by
5.2k points

1 Answer

8 votes

Answer:

1.
x^2-6x+8=0

2.
(x-4)(x-2)=0

3.
x=4 \text{ and } x=2

4.
x=4 \text{ and } x=2

Explanation:

1. When using substitution all we do would be is substituse the y for a 3.

This leaves us with the equation:


3=-x^2+6x-5

Rewriting it we get:

0=-x^2+6x-8

or if we shift the 0 to the other side:


x^2-6x+8=0

2. In order to factor the equation we can use the butterfly method:


\left[\begin{array}{ccc}1&-4\\1&-2\end{array}\right]
So it factors out to:


(x-4)(x-2)=0
You can also use the quadratic formula.

3. To find the solutions we just set each factor to 0

x-4=0\\\text{and}\\x-2=0
So the x-values would be:

x=4 \text{ and } x=2

4. To find the solution to the system we just plug in the values and it turns out to be the same numbers as before.

User Bogdan Dumitru
by
4.7k points